1999
DOI: 10.1021/jp991081s
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Argon Adsorption and SEM Characterization of C60 and C60/C70 Fullerenes:  Comparison with Graphite

Abstract: The surface and pore structure properties of the C60 and C60/C70 fullerene powders were studied by means of scanning electron microscopy, helium pycnometry, and 77.4 K nitrogen and argon adsorption. The pore structure of fullerene powders is macroporous and consists mainly of the voids between the fullerene aggregates. In the major part of the adsorption monolayer, both nitrogen and argon interactions with fullerenes are weaker than with graphite, possibly because of the reduction of the gas molecule−mirror im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…generally accepted N 2 cross-sectional area of 0.162 nm 2 [42]. Generally the prediction is in good agreement with experimental results [5], though there is relatively large deviation at high pressures. The deviation may be attributed to several factors: first, an empirical potential based on N 2 adsorption on graphite is used, which perhaps is not accurate; second, a rigid f.c.c.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…generally accepted N 2 cross-sectional area of 0.162 nm 2 [42]. Generally the prediction is in good agreement with experimental results [5], though there is relatively large deviation at high pressures. The deviation may be attributed to several factors: first, an empirical potential based on N 2 adsorption on graphite is used, which perhaps is not accurate; second, a rigid f.c.c.…”
Section: Introductionsupporting
confidence: 77%
“…The adsorption of N 2 [4][5][6], Kr [4], and Ar [6] near 77 K were measured and the isotherms were found to be of type II. The surface heterogeneity of the C 60 crystal has been examined by infrared spectroscopy of adsorbed CO, and the spectral shifts indicated that different types of adsorption sites exist on the surface [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Ismail and Rodgers studying Kr, N 2 , O 2 , and CO 2 adsorption, and Kaneko et al, using N 2 and O 2 adsorption, agreed in finding micropores in C 60 ; Ismail and Rodgers had already pointed out that surface area values might vary from one batch to another, depending on sample preparation and purification, as well as sample age. More recent work indicates, however, that fullerene powders with higher degrees of purity consist of nonporous particles. As expected for any solid, the porous texture of fullerenes is very sensitive to the synthesis and purification procedures followed in their preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been significant interest and effort in understanding the behavior of systems physisorbed onto spherical substrates [18][19][20][21][22][23][24][25][26][27], systems adsorbed onto Fullerenes [28][29][30][31][32][33][34] and even Fullerenes and their interactions [35][36][37][38][39][40][41][42][43][44][45][46],…”
Section: Introductionmentioning
confidence: 99%